Ciências Da Saúde: Teoria E Intervenção 4 2020
DOI: 10.22533/at.ed.08720230410
|View full text |Cite
|
Sign up to set email alerts
|

Journal Club Estratégia De Ensino E Aprendizagem: Avanço No Gerenciamento Em Enfermagem Baseada Na Prática

Abstract: Todo o conteúdo deste livro está licenciado sob uma Licença de Atribuição Creative Commons. Atribuição 4.0 Internacional (CC BY 4.0). O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores. Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Most studies found positive aspects of using the JC in terms of knowledge acquisition and transfer to clinical practice. However, according to Michelan and Spiri (2019), the evaluation of this pedagogical strategy is still scarce. In response to this weakness, and after three years of implementing this pedagogical strategy in undergraduate nursing students' clinical teaching (CT) settings, it is important to evaluate it, which was the purpose of this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies found positive aspects of using the JC in terms of knowledge acquisition and transfer to clinical practice. However, according to Michelan and Spiri (2019), the evaluation of this pedagogical strategy is still scarce. In response to this weakness, and after three years of implementing this pedagogical strategy in undergraduate nursing students' clinical teaching (CT) settings, it is important to evaluate it, which was the purpose of this study.…”
Section: Introductionmentioning
confidence: 99%
“…It was established as a teaching-learning strategy in medical education by Sir William Osler in 1875. Finding, sharing, and discussing texts makes it possible to incorporate scientific evidence into clinical practice (Michelan & Spiri, 2019).…”
Section: Introductionmentioning
confidence: 99%